Scanning electron microscopy (SEM)/Energy dispersive X-Ray (EDX) studies of the influence of a cobalt adhesion promoter on the interface between rubber skim compounds and tyre steel cord - Chandra A K; Bhowmick A K; Biswa A; Mukhopadhjyay R (Journal of Adhesion Science and Technology, 1996)
The failed interfaces between NR skim compounds and tyre steel cord used as tyre cord adhesion test specimens were studied by SEM and EDX analysis in order to understand the influence of cobalt boroacylate in the rubber compound as an adhesion promoter. SEM studies indicated a mixture of cohesive failure in the rubber and interfacial failure between the rubber and the brass coating. Cobalt boroacylate led to more cohesive failure of the rubber, due to its degradative effects on rubber. EDX analysis of the failed cord and rubber surfaces at various points gave the concentrations of copper, zinc, cobalt, iron, silicon, sulphur, oxygen and carbon. Assuming Van Ooijs model of interfacial sulphide film formation over the brass layer and analysing the EDX results, it was clear that the failure occurred at the Cu/Zn and CuxS/ZnS sub-layers.
Keywords: Rubber skim compound; Scanning electron microscopy; Tyre steel cord